Pengaruh Lingkungan Kerja Fisik dan Kelelahan Kerja Terhadap Kinerja Karyawan Pada PT. Wanapotensi Nusa Kabupaten Seram Bagian Barat - Tutupoho, Saleh; Rehatta, Pieter N. R.; Serang, Mohamad Ratmasa (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The Influence of Physical Work Environment and Fatigue on Employee Performance at PT. Wanapotensi Nusa, Seram Bagian Barat Regency. The purpose of this research is to determine the significant influence of the physical work environment on the performance of PT Wanapotensi Nusa employees, the significant influence of work fatigue on the performance of PT Wanapotensi Nusa employees. Based on the research, it can be concluded that the physical work environment has a significant effect on employee performance, seen from the results of the regression analysis showing that the t count of the physical work environment is 4,293 with a significance of 0.0 (significant), work fatigue has a significant effect on employee performance, seen from the results of the regression analysis showing that work fatigue has a t count of 5,553 with a significance of 0.0 (significant). The results of the R2 determination calculation obtained a value of 0.643, which means that 64%3 of the variation in employee performance can be explained by the physical work environment and work fatigue